Circles of sisterhood: formal and informal collaboration among American nuns in response to conflict with Vatican kyriarchy - Thompson, Margaret Susan (Journal of feminist studies in religion, 2016)
In this essay, Margaret Thompson explores the Vatican's Apostolic Visitation of Catholic women religious (sisters/nuns) in the United States (2009–2014), analyzing both its untoward interference in American congregations and how sisters' experiences with prior conflicts have shaped—and strengthened—their capacity to resist and respond. Specifically, Thompson's analysis focuses on the increasingly collaborative and consensual basis for sisters' exercise of spiritual and political agency, including their growing openness to participation by sisters not in leadership, by grassroots Catholics, and by popular (especially feminist, including non-Catholic) supporters. It is grounded in both feminist organizational theory and feminist theology/spirituality, particularly sisters' explicit resistance to what Elisabeth Schüssler Fiorenza has designated kyriarchy: a social system or set of connecting social systems built around domination, oppression, and submission. Thompson derives her evidence not only from her extensive research into the history and contemporary dimensions of American religious life but also her interviews with and access to sister-participants in both the current controversy and its precursors.